Interleukin-1 inhibition facilitates recovery from liver injury and promotes regeneration of hepatocytes in alcoholic hepatitis in mice - Iracheta-Vellve, Arvin (Liver Int, 2017)
BACKGROUND & AIMS: Inflammation and impaired hepatocyte regeneration contribute to liver failure in alcoholic hepatitis (AH). Interleukin (IL)-1 is a key inflammatory cytokine in the pathobiology of AH. The role of IL-1 in liver regeneration in the recovery phase of alcohol-induced liver injury is unknown. METHODS: Here we tested IL-1 receptor antagonist to block IL-1 signaling in a mouse model of acute-on-chronic liver injury on liver inflammation and hepatocyte regeneration in AH. RESULTS: We observed that inhibition of IL-1 signaling decreased liver inflammation, neutrophil infiltration, enhanced regeneration of hepatocytes, and resulted in increased rate of recovery from liver injury in AH. CONCLUSION: Our novel findings suggest that IL-1 drives sustained liver inflammation and impaired hepatocyte regeneration even after cessation of ethanol exposure.